Surface Reapplication of Lime and Gypsum on Maize Cultivated Sole and Intercropped with Urochloa - Bossolani, J. W. [UNESP]; Lazarini, E. [UNESP]; Santos, F. L. [UNESP]; Sanches, I. R. [UNESP]; Meneghette, H. H. A. [UNESP]; Parra, L. F. [UNESP]; Souza, L. G. M. [UNESP] (Taylor & Francis Inc, 2018)
The aim of this experiment was to study the lime and gypsum reapplied on surface and their impacts on maize crop under the sole and intercropped systems. The experiment is being developed in a dystrophic Oxisol, since 2011, and arranged in a randomized blocks design, in split-split plots, with four replications. As treatments in the plots, the maize was installed in two cropping systems: sole and intercropped with Urochloa. For the subplots, we used four doses of lime (0, 2000, 4000, and 6000 kg ha(-1)) and four doses of gypsum (0, 1500, 3000, and 4500 kg ha(-1)) distributed at random in the sub-subplots. The combination of intermediate doses of lime and gypsum resulted in higher foliar Ca content. The grain yield increased with the combination of lime and gypsum. The maize when cultivated in intercropped system is more productive, with a point of maximum for dolomitic lime of 3031 kg ha(-1).
Keywords: Cropping systems; lime and gypsum application; mineral nutrition